PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN DI GRAMEDIA MANADO - Desilsan ., Tansala; Johny Revo Elia Tampi; Joanne Valesca Mangindaan (AGRI-SOSIOEKONOMI, 2021)
This study aims to determine whether the marketing mix (products, prices, promotions, distribution places/channels, people, processes and physical facilities) simultaneously influence purchasing decision at Gramedia Manado. This research was conducted at Gramedia Bookstore, Jl. Sam Ratulangi No. 45, South Wenang, Manado City. This research was conducted from October to November 2020. This research is a quantitative study with a descriptive approach to see causal relationships. This study uses primary and secondary data. Primary data is the result of direct data collection from informants by distributing questionnaires to 100 respondents who have made at least two purchases at Gramedia Manado. Secondary data is obtained from existing sources (books, journals, websites, etc.) for reference in making reports. Data analysis used multiple regression analysis. The results showed that the marketing mix simultaneously had an effect and was significant on purchasing decisions at Gramedia Manado.*eprm*